Identifying Cross-Sided Liquidity Externalities - Johannes A. Skjeltorp; Elvira Sojli; Wing Wah Tham (Tinbergen Institute, 2013)
We study the relevance of the cross-sided externality between liquidity makers and takers from the two-sided market perspective. We use exogenous changes in the make/take fee structure, minimum tick-size and technological shocks for liquidity takers and makers, as experiments to identify cross-sided complementarities between liquidity makers and takers in the U.S. equity market. We find that the externality is on average positive, but it decreases with adverse selection. We quantify the economic significance of the externality by evaluating an exchange's revenue after a make/take fee change.
Keywords: G10; G20; G14; 330; Liquidity cycle; Liquidity externality; Two-sided markets; Make/take fees; Marktliquidität; Externer Effekt